2006
DOI: 10.1111/j.1365-313x.2005.02622.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of Arabidopsis NCED6 and NCED9 genes indicates that ABA synthesized in the endosperm is involved in the induction of seed dormancy

Abstract: SummaryThe cleavage of 9-cis-epoxycarotenoids to xanthoxin, catalyzed by 9-cis-epoxycarotenoid dioxygenases, is considered to be the key regulatory step of abscisic acid (ABA) biosynthesis. In Arabidopsis, genes for these enzymes form a multigene family with nine members, only five of which are thought to be involved in ABA production. In contrast to the prominent function of AtNCED3 in stress responses, the physiological and developmental role of the other 9-cis-epoxycarotenoid dioxygenases (NCEDs) remain unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
386
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 417 publications
(406 citation statements)
references
References 38 publications
(70 reference statements)
17
386
0
3
Order By: Relevance
“…At the transcript level, the endosperm also expresses many genes required for ABA synthesis and catabolism, suggesting that the endosperm might also be able to make and degrade ABA. This has been further demonstrated by a recent report that two carotenoid cleavage dioxygenase isoforms are expressed in the endosperm of maturing seeds and are required for dormancy (Lefebvre et al, 2006). One of these, NCED9, was still expressed in an endosperm-specific manner in germinating seeds (Table 3).…”
Section: Aba and Ga Synthesis And Response In The Embryo And Endospermmentioning
confidence: 53%
See 1 more Smart Citation
“…At the transcript level, the endosperm also expresses many genes required for ABA synthesis and catabolism, suggesting that the endosperm might also be able to make and degrade ABA. This has been further demonstrated by a recent report that two carotenoid cleavage dioxygenase isoforms are expressed in the endosperm of maturing seeds and are required for dormancy (Lefebvre et al, 2006). One of these, NCED9, was still expressed in an endosperm-specific manner in germinating seeds (Table 3).…”
Section: Aba and Ga Synthesis And Response In The Embryo And Endospermmentioning
confidence: 53%
“…The endosperm is also vital for normal seed dormancy and may be the principal site for the synthesis of dormancy inducing ABA during seed development (Lefebvre et al, 2006). It is possible that the reduced ABA response observed in the endosperm has evolved as a consequence of higher endogenous levels of ABA in that tissue.…”
Section: The Endosperm Is Required For Aba and Ga Regulation Of Seed mentioning
confidence: 99%
“…In this study, we found that expression of NCED2, NCED5, and NCED9 was up-regulated by high temperature in after-ripened seeds under continuous illumination. NCED6 and NCED9 are responsible for ABA synthesis during seed development and dormancy (Lefebvre et al, 2006). In contrast to NCED9, NCED6 showed weak expression during imbibition, and T-DNA insertion mutants of NCED6 showed no resistance to thermoinhibition (Supplemental Fig.…”
Section: Regulation Of Aba Biosynthesis By High Temperature In Seedsmentioning
confidence: 99%
“…In lettuce seeds, thermoinhibition is alleviated by removing or puncturing the endosperm . From spatial expression analysis of NCED genes during development of Arabidopsis seeds, Lefebvre et al (2006) suggested that ABA synthesized in the endosperm contributes to the induction of seed dormancy. We found that expression of NCED9 was predominant over other NCED genes in the embryo, whereas NCED5 expression was predominant in the endosperm of thermoinhibited seeds (Fig.…”
Section: Nced5 Protein In Vitro (Supplementalmentioning
confidence: 99%
See 1 more Smart Citation